The functional activity of the miR-1914-5p in lipid metabolism of the hepatocarcinoma cell line HepG2: a potential molecular tool for controlling hepatic cellular migration - Silveira, Marina Bonfogo da [UNESP]; Pansa, Camila Cristiane [UNESP]; Malaspina, Osmar [UNESP]; Moraes, Karen C. M. [UNESP] (Springer, 2021)
Hepatocellular carcinoma is one of the most common types of cancer in the world with high mortality rate and new therapies that control of fatty acid metabolism may limit the proliferation of cancer cells. In the last two decades, the non-coding RNAs have been considered as promising molecular tools to treat diseases, because they are able to modulate gene expression and the metabolic routes; however, deep investigation of their mechanistic behavior in pathologies must be performed. Thus, our aim was to evaluate the modulatory effect of the miR-1914-5p in controlling lipid metabolism in HepG2, a widely used human hepatocarcinoma cell line. The molecular and cellular analyses demonstrated that the functional inhibition of the investigated microRNA completely changed the cellular metabolism and behavior, compared to control groups. The in vitro inhibition of the miR-1914-5p increased the energy expenditure pointed in different analyses, decreasing cell doubling time and migration rate verified in wound healing and in the classical transwell chambers invasion assays, which makes the miR-1914-5p a candidate for further translational and preclinical studies to validate its function in controlling metastasis in liver cancer or even treat those diseases.
Keywords: Cell migration; Cellular mechanisms; Hepatic disease; Lipid metabolism; Non-coding RNAs; Systems biology